ANALYSIS OF THE EFFECT OF WORK CLIMATE AND WORK SPIRIT ON EMPLOYEE EFFECTIVENESS AT THE MANPOWER AND TRANSMIGRATION DEPARTMENT OF EAST OKU - Feriyana, Winda (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This review expects to dissect to some extent or together the impact of work environment, work energy on worker work viability and investigate the most predominant factors in affecting representative work adequacy at the East OKU Labor and Immigration Office, the aftereffects of relapse examination and the relationship between's work environment and worker work adequacy shows the relapse model = 16,385 + 0.666X1 + e with a connection coefficient of 0.479. The aftereffects of the relapse examination and the relationship between's work enthusiasm and worker work adequacy showed the relapse model = 21.077 + 0.578X2 + e with a connection coefficient of 0.673. The aftereffects of numerous relapse investigation and the relationship between's work environment and work energy together on work adequacy show the relapse model = 3.026 + 0.553X1 + 0.533X2 + e with a connection coefficient of 0.780. From the various straight relapse condition above, it shows that the work environment variable (X1) has a more predominant impact on representative work adequacy than work energy. This examination was led on 28 respondents with the logical technique utilized is way investigation utilizing SPSS programming. Keywords: Work climate, work passion, work effectiveness